THE ROLE OF PARENTS AND TEACHERS IN CHARACTER BUILDING OF CHILDREN AT SD INPRES LANGAWAI, LIDI VILLAGE, PALUE DISTRICT - Hermus Hero (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Education plays an important role in building the quality of life for Indonesians, especially through character building from an early age. Character education aims to instill moral values and good behavior, such as politeness, honesty, and religiosity. However, the role of parents in character building at SD Inpres Langawai, Lidi Village, Palue District, has not been optimal. Observations show poor student behavior, such as a lack of discipline and respect for teachers, which is caused by the limited involvement of parents in guiding their children at home. Economic factors lead parents to focus more on meeting basic needs, leaving character education of children largely to the school. This research uses a qualitative approach with a case study method to describe the role of parents and teachers in shaping children's character. Data were collected through observations, interviews, and documentation. The research results show that parents tend to direct children through words without providing real examples. Teachers at SD Inpres Langawai play a significant role in educating students' character through various educational programs, although parental support is crucial to achieving optimal results. Collaboration between parents and teachers is needed to create a conducive environment for strong character development in children so that they can grow into individuals who contribute positively to society. This study emphasizes the importance of communication and cooperation between parents and teachers in effectively shaping children's character.